Effect of occlusal splint thickness on electrical masticatory muscle activity during rest and clenching - Pita, Murillo Sucena; Ribeiro, Adriana Barbosa; Garcia, Alicio Rosalino [UNESP]; Pedrazzi, Vinicius; Zuim, Paulo Renato Junqueira [UNESP] (Sociedade Brasileira de Pesquisa Odontológica (SBPqO), 2011)
The extent of separation between the maxillary and mandibular teeth in the fabrication of interocclusal splints designed to achieve efficiency and muscle relaxation is controversial and undefined in the literature. Based on this premise, the aim of this study was to evaluate the effect of interocclusal splint thicknesses of 3 and 6 millimeters on the electrical activity of the anterior temporal and masseter muscles during rest and dental clenching. Twenty asymptomatic individuals (10 males and 10 females) were selected using the Research Diagnostic Criteria (RDC). Electromyography (EMG) was performed both with and without the 3- and 6-mm splints using the Bio EMG software package, which recorded values given in microvolts (mu V). The results, which were assessed using analysis of variance (ANOVA) to a 5% significance level (p < 0.05), showed increased electrical activity of the masticatory muscles during dental clenching compared with at rest, with greater activity in the masseter muscle. The electrical activity did not differ according to the thickness of the splints or between males and females. We can conclude that both splint thicknesses are effective in treating muscle hyperactivity given their similar clinical behavior for asymptomatic individuals.
Keywords: Electromyography; Temporal Muscle; Masseter Muscle; Occlusal Splints; Dental Occlusion